2014
DOI: 10.4300/jgme-d-13-00461.1
|View full text |Cite
|
Sign up to set email alerts
|

Restoring Emphasis on Ambulatory Internal Medicine Training—The 3∶1 Model

Abstract: Background Resident dissatisfaction in ambulatory care training has prompted the need for new scheduling models that support a positive learning climate. Intervention We instituted a 3∶1 scheduling model for postgraduate year (PGY)–2 and PGY-3 residents. We hypothesized this model would provide a more structured ambulatory educational atmosphere, better continuity of care, and more exposure to subspecialty outpatient medicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 11 publications
0
29
0
Order By: Relevance
“…Programmatic restructuring interventions described by Harrison et al, 12 Chaudhry et al, 13 Warm et al,, 17 and Lofgren and Mladenovic 15 all resulted in statistically significant increases in resident satisfaction. In contrast, the restructuring intervention described by Wieland et al 18 did not influence resident satisfaction.…”
Section: Interventional Studies On Scheduling and Reorganizationmentioning
confidence: 92%
See 2 more Smart Citations
“…Programmatic restructuring interventions described by Harrison et al, 12 Chaudhry et al, 13 Warm et al,, 17 and Lofgren and Mladenovic 15 all resulted in statistically significant increases in resident satisfaction. In contrast, the restructuring intervention described by Wieland et al 18 did not influence resident satisfaction.…”
Section: Interventional Studies On Scheduling and Reorganizationmentioning
confidence: 92%
“…1). While most studies evaluated a single residency program (Barnett et al, 11 Harrison et al, 12 Chaudhry et al, 13 Hochman et al, 14 Lofgren et al, 15 Roth et al, 16 Warm et al, 17 Wieland et al 18 ), two studies each evaluated three residency programs (Sisson et al 19 and Percoralo et al 1 ) and one study evaluated 36 internal medicine programs (Serwint et al 20 ). There was no uniform survey tool used to assess satisfaction among this group of studies.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[29][30][31] Several studies focused on resident satisfaction with an overall trend toward improvement in reducing inpatient-outpatient conflict 30,[32][33][34][35] and resident satisfaction with ambulatory education, 30,33,36 but no studies found an increase in the desire to pursue primary care careers. 29,32,36 Only 2 studies evaluated improvement in quality of care in X þ Y schedules with mixed results. 31,37 Shalaby and colleagues 38 provided a practical review of crafting X þ Y schedules.…”
Section: Clinic Redesignmentioning
confidence: 99%
“…With the introduction of duty hour restrictions and emphasis on improved ambulatory training (16), many internal medicine residency programs have undertaken substantial scheduling changes (1719), resulting in increased resident exposure to multispecialty outpatient care (18). The University of Pennsylvania internal medicine residency program recently adopted a 6+2 scheduling model.…”
Section: Nephrology Curriculum Implementationmentioning
confidence: 99%